HUBUNGAN MUTU PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI BADAN LAYANAN UMUM DAERAH RUMAH SAKIT UMUM KABUPATEN BOMBANA - Salfia Salfia; Sartiah Yusran; Juminten Saimin (NHM PRESS, 2021)
Health services in various installations, especially services in inpatient unit installations, must be able to satisfy every service user in accordance with the average level of patient satisfaction and its implementation in accordance with the code of ethics and service standards applied. The results showed that: first, there was a significant relationship between reliability and patient satisfaction with value (ρ value = 0.000 <0.05), secondly there was a significant relationship between assurance and patient satisfaction with a value (ρ value = 0.000 <0.05). ), thirdly there is a significant relationship between physical evidence and patient satisfaction with a value (ρ value = 0.000 <0.05), fourth there is a significant relationship between attention and patient satisfaction with a value (ρ value = 0.000 <0.05), fifth there is a significant relationship between responsiveness and patient satisfaction with a value (ρ value = 0.000 <0.05). This shows that the relationship of reliability, assurance, physical evidence, attention and responsiveness of officers in providing services and education to patients at the Regional Public Service Agency of the Bombana Regency General Hospital can affect the level of patient satisfaction.